Menganalisis Sekolah Dasar Sebagai Organisasi Pendidikan Sistem Sosial - Idawati Idawati; Nurul Muhklisah; Hardianto Hardianto; Nurul Hidayah; Armawanti Yuanata; Suratmi Dahlan (Mathematics Education Study Program, 2025)
Schools as institutions must be open and adaptable to external changes in order to remain effective and sustainable especially in today's modern society where schools must function as both social and cultural systems. Through proper education, both individual and social aspects can develop in harmony, aligning with Indonesia’s motto —Unity in Diversity. Modern society is characterized by rational thinking, future-oriented perspectives, time consciousness, openness, and objective reasoning. Based on this background, this paper aims to examine schools as a system of social interaction. This study employs a qualitative approach, with data collected from relevant literature, including books, journals, and interviews. School is a concept with a dual meaning. First, it refers to a building or physical environment with all its facilities, serving as a place where a specific group of people undergoes a particular educational process. Thus, when we hear the word